Report on Proceedings of the Ninth Annual European CME Forum, Amsterdam, the Netherlands, November 2016. Issue 1 (1st January 2017) - Murray, Ron
ABSTRACT: Participants from as far afield as Australia and North America convened in Amsterdam, the Netherlands between 9 and 11 November 2016 to attend the Ninth European CME Forum (ECF). The meeting combined panel discussions with a range of presentations on topics such as high quality learning, current challenges in CME and future trends. However, the bulk of the forum was taken up with interactive workshops under three different track headings: Development, Educational Design and the CME Environment. Attendees also heard from a group of CME pioneers in a pre-conference session on the history of CME on both sides of the Atlantic Ocean.